Ecologia populacional de Euterpe edulis e os efeitos da introdução de Euterpe oleracea na floresta atlântica no Estado de São Paulo - Tibério, Fernanda Cristina dos Santos (2011)
The main objectives of this dissertation were to evaluate the risks of introduction of Euterpe oleracea in the Atlantic Rainforest and its influence over a native population of Euterpe edulis. We investigated the ecological and morphological features of these species also including pre-existing data about hybrids experimentally produced between them (Chapter 1). We did the populations sampling in two areas of Atlantic Rainforest, in southern São Paulo state: Carlos Botelho State Park (CBSP) and Ilha do Cardoso State park (ICSP). At CBSP, we sampled the co-occurring populations of E. edulis and E. oleracea and at ICSP we sampled the control population for E. edulis, which is free from E. oleracea introduction. We evaluated the characteristics of growth in diameter and height of these populations and its ontogenetic stages through the allometric relationships between diameter and height (Chapter 2). We also analyzed population ecology and distribution of these three species (Chapter 3). For the co-occurring populations we evaluated the fruit biometry and observed the frugivorous bird community (Chapter 3). Our results indicated that two Euterpe species may be well represented for the same ontogenetic stages and the three studied populations presented similar allometry. Concerning to population ecology we observed that E. edulis population at CBSP presents total individuals density lower that ICSP population. Both E. edulis populations do not show a significant aggregation. Population of E. oleracea shows a reduced N, high aggregated distribution and is also capable of dispersing itself outside the original range of plantation. We also observed that these species produce morphologically similar fruits but with different sizes, with bigger fruits from E. oleracea and smaller from hybrids. Finally, we detected that E. oleracea shares the same guild of frugivorous birds and may displace dispersers from E. edulis. We concluded that E. oleracea is capable to successfully establish, reproduce and disperse itself and, thus, it is an invasive species in Atlantic Rainforest. Its introduction affects ecological processes linked to pollination, gene fluxes and frugivore and seed dispersion. These changes may be related to genetic mixtures of populations and decreasing of population of E. edulis. Finally, the introduction of E. oleracea may perform one more threat to maintenance of E. edulis populations, which are already threatened by over exploitation.